Offshore safety management : implementing a SEMS program - Sutton, Ian S. (William Andrew, 2012)
2010 was a defining year for the offshore oil and gas industry in the United States. On April 20th 2010 the Deepwater Horizon (DWH) floating drilling rig suffered a catastrophic explosion and fire. Eleven men died in the explosion - seventeen others were injured. The fire, which burned for a day and a half, eventually sent the entire rig to the bottom of the sea. The extent of the spill was enormous, and the environmental damage is still being evaluated. Following DWH the Bureau of Ocean Energy Management, Regulations and Enforcement (BOEMRE) issued many new regulations. One of them is the Safety and Environmental System (SEMS) rule, which is based on the American Petroleum Institute's SEMP recommended practice. Companies have to be in full compliance with its extensive requirements by November 15th, 2011. Ian Sutton's book provides an experienced engineer's perspective on the new SEMS regulations for offshore oil & gas drilling, how they compare to prior regulations and how to implement the new standards seamlessly and efficiently. Sutton explains the new SEMS rule, and describes what must be done to achieve compliance. Each of the twelve elements of the SEMS rule (such as Management of Change and Safe Work Practices) is described and guidance is provided as to what needs to be done to meet BOEMRE requirements. The book goes beyond the immediate requirements of SEMS. It provides guidance to anyone who is responsible for implementing or running an offshore safety management program, regardless of location or regulatory environment. For example, two chapters discuss Safety Cases and Formal Safety Assessments - techniques that are used worldwide. UNIQUE FEATURES AND BENEFITS: . Detailed explanation of how to implement the new SEMS standard for offshore operations. . Ties the new regulations in with existing Safety Management approaches helping managers leverage existing processes and paperwork. . Written by a well-respected authority in the field (quotes from reviews: 'vast expertise', 'Ian has insider access to executive thinking that few others have', 'Ian is a well known figure in the process safety industry and is well regarded'). . CEOs now have to sign off on compliance paperwork, making SEMS implementation something you need to get right first time. Ian Sutton provides the expert insights you need to achieve this. . Detailed explanation of how to implement the new SEMS standard for offshore operations. . Ties the new regulations in with existing Safety Management approaches helping managers leverage existing processes and paperwork. . Written by a well-respected authority in the field (quotes from reviews: 'vast expertise', 'Ian has insider access to executive thinking that few others have', 'Ian is a well known figure in the process safety industry and is well regarded'). . CEOs now have to sign off on compliance paperwork, making SEMS implementation something you need to get right first time. Ian Sutton provides the expert insights you need to achieve this.